1982
DOI: 10.1007/bf02327040
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell glutathione peroxidase in simple trisomy 21 and translocation 21/22

Abstract: A portion of the observed variation in SCE frequencies among primates might be the result of inherent differences in BrdUrd incorporation. Stetka and Carrano 12 found that the BrdUrd/base pair ratio correlated well with SCE frequency. The incorporation of BrdUrd is not linearly proportional to the molarity of BrdUrd in the culture medium, while the BrdUrd induced SCE frequencies are linearly proportional to the percentage substitution of BrdUrd for 543 dThd 13. It appears that BrdUrd competes with dThd for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In adult patients the erythrocyte glutathione peroxidase activity increases by 5%. These values are comparable with those obtained by Neve et al (10), and are slightly lower than those reported earlier in which glutathione peroxidase act ivity in Down's syndrome patients was found to be 139-156% ofthat in healthy controls (11,12). Probably the increase of glutathione perpxidase activity in erythrocytes is the secondary result of a regulatory mechanism involving an increased activity of superoxide dismutase and intensified production of H 2 O 2 in trisomy 21 cells (9), Elevated glutathione peroxidase activity in Down's syndrome patients could be a useful protective mechanism against peroxidative cell damage.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In adult patients the erythrocyte glutathione peroxidase activity increases by 5%. These values are comparable with those obtained by Neve et al (10), and are slightly lower than those reported earlier in which glutathione peroxidase act ivity in Down's syndrome patients was found to be 139-156% ofthat in healthy controls (11,12). Probably the increase of glutathione perpxidase activity in erythrocytes is the secondary result of a regulatory mechanism involving an increased activity of superoxide dismutase and intensified production of H 2 O 2 in trisomy 21 cells (9), Elevated glutathione peroxidase activity in Down's syndrome patients could be a useful protective mechanism against peroxidative cell damage.…”
Section: Discussionsupporting
confidence: 62%
“…In erythrocytes the Se concentration increase is not significant. The observed decrease of Se concentration in trisomy 21 patients has no influence upon its bioavailability, as the activity of glutathione peroxidase does not differ from that of the control group (12,13,14,20).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In DS erythrocytes, glutathione peroxidase activity is significantly increased along with that of SOD-1 (Sinet et al, 1975;Frischer et al, 1981;Kedziora et al, 1982), while catalase levels are normal (Pantelakis et al, 1972). This is believed to be an adaptive response to the elevated levels of hydrogen peroxides produced by the augmented SOD-1 activity, rather than a gene dosage effect, since the gene coding for GSHPx is located on human chromosome No.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased SOD activity, many studies have reported increased activity of GSH-Px in various tissues of individuals with DS 6,7,11,13,16,[28][29][30][31][32][33] , as well as in animal models 18 . Because Wijnen and colleagues 34 have localised the gene for GSH-Px on chromosome 3, its increase in individuals with DS is not a gene dose effect.…”
Section: Compensatory Increase In the Activity Of Glutathione Peroxidmentioning
confidence: 99%